Eksplorasi Kesahihan Hadis dalam Tradisi Sufi Aceh: Studi Kasus Majelis Pengkajian Tauhid dan Tasawuf Indonesia - Mawardi, Mawardi; Drajat, Amroeni; Sulidar, Sulidar (AL QUDS : Jurnal Studi Alquran dan Hadis, 2023)
Exploring the Authenticity of Hadith in the Sufi Tradition of Aceh: A Case Study of the Majelis Pengkajian Tauhid dan Tasawuf IndonesiaThis article explores the Majelis Pengkajian Tauhid dan Tasawuf Indonesia (MPTT-I), a Sufi group, and its critique of Hadith. Drawing on data from the book "Ajaran Tauhid Tasawuf dan Tauhid Sufi," it identifies several Hadith used by MPTT-I, which hadith scholars classify as fabricated. Despite their dubious status, MPTT-I employs these Hadith to substantiate their Sufi teachings. Theoretical disparities in standards for authenticating Hadith between Hadith scholars and Sufi scholars prompt an inquiry: Does MPTT-I lean towards the Sufi scholars' method, involving kashf, or the Hadith scholars' method, prevalent among Acehnese scholars, or do they strike a balance by internalizing the Sufi scholars' approach for teaching while deploying the Hadith scholars' method as a negotiation strategy with the majority's teachings? To answer this, data from interviews and documentation are subjected to content analysis and an interdisciplinary approach. Findings reveal that MPTT-I's Hadith criticism method differs from both Sufi and Hadith scholars. They eschew the kashf method, prioritizing content quality over the chain of narration (sanad). Moreover, MPTT-I accords equal importance to the authority of core and ancillary texts when assessing Hadith quality, especially in legitimizing their Sufi teachings.